Environmental industry and regional policy in Hungary - Fodor, István (Acta Agraria Debreceniensis, 2012)
The paper attemps to define environmental industry. The author has searched the history and background of the rapid development of this process. The study analyses the present and future regional development potential of environmental industry in Hungary.